Prognostic factors in salvage surgery for recurrent head and neck cancer: A systematic review and meta-analysis. (January 2022) - Lupato, Valentina; Giacomarra, Vittorio; Alfieri, Salvatore; Fanetti, Giuseppe; Polesel, Jerry
Graphical abstract: This systematic review and meta-analysis summarizes the association of pre-surgery and postsurgery factors with poor overall survival or progression free-survival (significant pooled hazard ratios were reported in red) in patients undergoing salvage surgery for recurrent head and neck cancer . The identification of pre-surgery factors associated with poor outcomes may help clinicians in the selection of the best candidate to salvage surgery, whereas post-surgery factors may help to tailor post-surgery surveillance. Highlights: Patients aged >60 years or with initial advanced stage have high risk of death. Early recurrence and regional recurrence double the risk of death. Patients with positive surgical margins have twice the risk of negative outcomes. Extracapsular extension and perineural invasion are predictors of poor survival. Alternative approaches to salvage surgery may be considered for high-risk patients. Abstract: Introduction: Although salvage surgery (SS) is considered the best curative choice in recurrent head and neck cancer, the identification of patients who can benefit the most from this treatment is challenging. Methods: We systematically reviewed the prognostic role of pre- and post-surgery factors in patients undergoing SS for recurrent head and neck cancer (oral cavity, oropharynx, hypopharynx, and larynx). Results: Twenty-five studies met the inclusion criteria out of 1280 screened citations. Pre-surgery factors significantly associated with worse overall survival were age>60 years, advanced initial stage, early recurrence, and regional recurrence; no heterogeneity between study emerged. Among post- surgery factors, worse survival emerged for positive surgical margins, extracapsular extension and perineural invasion. Conclusion: The identification of pre-surgery factors associated with poor outcomes may help the selection of the best candidate to SS; alternative treatments should be considered for high-risk patients. Post-surgery predictors of worse prognosis may guide clinicians in tailoring patients' surveillance.